2009
DOI: 10.1371/journal.pone.0008247
|View full text |Cite
|
Sign up to set email alerts
|

Regional Brain Stem Atrophy in Idiopathic Parkinson's Disease Detected by Anatomical MRI

Abstract: Idiopathic Parkinson's disease (PD) is a neurodegenerative disorder characterized by the dysfunction of dopaminergic dependent cortico-basal ganglia loops and diagnosed on the basis of motor symptoms (tremors and/or rigidity and bradykinesia). Post-mortem studies tend to show that the destruction of dopaminergic neurons in the substantia nigra constitutes an intermediate step in a broader neurodegenerative process rather than a unique feature of Parkinson's disease, as a consistent pattern of progression would… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
50
1
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 31 publications
8
50
1
2
Order By: Relevance
“…This may be the first identifiable stage of the disease. In their patients the white matter gets atrophy by aging but there was no evidence of atrophy in gray and white matter of the brainstem (40). The results of the current study showed there were no significant differences in brainstem volumes between PD patients and control group.…”
Section: Discussioncontrasting
confidence: 53%
“…This may be the first identifiable stage of the disease. In their patients the white matter gets atrophy by aging but there was no evidence of atrophy in gray and white matter of the brainstem (40). The results of the current study showed there were no significant differences in brainstem volumes between PD patients and control group.…”
Section: Discussioncontrasting
confidence: 53%
“…37,38 In addition, some reports showed no differences between PD and controls. 39,40 Differences in the relative representation of the PIGD and TD subtypes may explain the disparate findings in these earlier reports. Our findings highlight the need to distinguish among the clinical subtypes when investigating the neural correlates underlying PD.…”
Section: Resultsmentioning
confidence: 80%
“…Conventional and advanced MR studies have recently reported an involvement of the pontomedullary brainstem in PD [11,24,25], but also in other a-synuclein pathologies such as dementia with Lewy bodies or idiopathic rapid-eye-movement sleep disorder [26]. Jubault and colleagues [11] described a comparable pattern of brainstem abnormalities in 23 PD patients at Hoehn and Yahr stages I-II compared to healthy controls in a group level analysis that corresponds very closely to our results (peak significance in MNI space: -1, -36, -49; volume 4,287 mm 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…The first study demonstrating in vivo that conventional T1-weighted MR imaging is able to detect white matter (WM) atrophy in the pontomedullary junction in mild-tomoderate PD was performed by Jubault and colleagues using voxel-based morphometry [11].…”
Section: Introductionmentioning
confidence: 99%